Ethyl 2-(2-methyl-1H-benzimidazol-1-yl)acetate - Xu, Guang-Hai (International Union of Crystallography, 2008)
A new benzimidazole compound, C(12)H(14)N(2)O(2), has been synthesized by the reaction of 2-methyl-1H-benzimidazole and ethyl 2-bromoacetate. In the crystal structure, weak intermolecular C—H⋯N hydrogen bonds link the molecules into chains. π⋯π Contacts (centroid⋯centroid distance = 3.713 Å) are observed. A C—H⋯π interaction is also present. The N—C—C—O torsion angle is 178.4 (2)°.